Risk Assessment in PT INTI (Persero) or PLTS Project (The Indonesian Journal of Business Administration, 2020)
PT. INTI (Persero) has a business line consisting of manufacture assembly, managed service, digital service, and system integrator. In the system integrator, there is one business in the form of solar panels or solar power (PLTS). Until now, PT INTI (Persero) has completed several projects related to PLTS, which include projects from Ministries, BUMN, regional government, and also from the private sector. In order to complete the project by achieving the specified target without any delay or other obstacles, in this case the Company is planning to carry out an assessment related to the risks that may appear. In completing various projects related to PLTS, there are many risks that can affect the completion of a project. If this risks is not mitigated, the company will have a negative impact which will make the target not achieved from the contribution margin. In order to complete the project by achieving the specified target without any delay or other obstacles, in this case the Company is planning to carry out an assessment related to the risks that may appear. The company plans to analyze the risk that can affect the project, so PT INTI (Persero) can mitigate the risk to maintain the project margin in PLTS for 2020. Afterall, if the Company can mitigate the risk, so the target that already set will be achieved by the Company. The analysis will be using analytical hierarchy process (AHP). After the analysis, there is no high or very high issues. Sub criteria like customer, coaching and development, recording, organizational, tender rules are at low level of risk. Sub criteria like selling product, selling price, supporting documents, business scheme, market/competition, accounts receivable, exchange, budgeting, coaching and development, work accidents, process, quality, purchase price, shipping/arrival, planning, implementation, reporting are at medium level of risk. Based on that, we accept 5 risk factors because low level, and reduce 16 risks for the medium level. Keywords: analytical hierarchy process, risk management, PLTS